Social value of public information: testing the limits to transparency - Michael Ehrmann; Marcel Fratzscher (European Central Bank (ECB), 2007)
Transparency has become an almost universal virtue among central banks. The paper tests empirically, for the case of the Federal Reserve, two hypotheses about central bank transparency derived from the debate of Morris and Shin (2002) and Svensson (2006). First, the paper finds that the precision of communication is a key determinant of the predictability of both FOMC decisions as well as the future policy path. Second, the effectiveness of communication is found to depend on the market environment. Specifically, a given statement may enhance predictability in an environment of high market uncertainty, but may reduce it when uncertainty is low. The findings underline the limits to transparency and stress the need for communication to be flexible and adjust to market conditions in order for central banks to achieve their ultimate objectives.
Keywords: E52; E58; D82; 330; communication; effectiveness; Federal Reserve; monetary policy; Predictability; transparency; Geldpolitik; Zentralbank; Glaubwürdigkeit; Vertrauen; Zinspolitik; Theorie; USA